Diarrhea Prevalence and Sociodemographic Factors among Under-Five Children in Rural Areas of North Gondar Zone, Northwest Ethiopia. (3rd June 2018) - Getachew, Atalay; Guadu, Tadesse; Tadie, Alebachew; Gizaw, Zemichael; Gebrehiwot, Mulat; Cherkos, Daniel Haile; Menberu, Martha Alemayehu; Gebrecherkos, Teklay
Abstract : Background . Diarrheal disease remains one of the principal causes of morbidity and mortality in infants and children in developing countries, including Ethiopia. Risk factors for diarrhea vary by settings and have important implications for developing intervention strategies to reduce the burden of the disease. Thus, the aim of this study was to assess diarrhea prevalence and sociodemographic factors among under-five children in rural areas of North Gondar Zone. Methods . A community-based cross-sectional study was conducted from April to June 2016 among 736 randomly selected households with one child under five years old. A structured questionnaire was used for collecting information on sociodemographic characteristics and diarrheal occurrence. Data was analyzed using SPSS version 20. The bivariate and multivariable logistic regression analysis were used to determine the association between risk factors and diarrheal occurrence, and a p value < 0.05 was taken as statistically significant. Results . A total of 736 under-five children and their respondents were enrolled during the study period. Almost all respondents were biological mothers 96.4% (709/736), married 94.2% (693/736), and house wives 86% (632/736). The overall prevalence of diarrheal disease among under-five children was 22.1% (163/743). Of these, children with age group of less than one year old, 7.7 % (57/736), were commonly infected with diarrheal diseases. Children less than or equal to one year [AOR=1.82, 95% CI= (1.39, 4.63)], guardians [AOR=4.37, 95% CI= (1.73, 11.1)], and children with no breast feeding practice [AOR=3.13, 95% CI= (1.62, 6.03)] were the major risk factors for the occurrence of diarrhea. Conclusion . Childhood diarrhea remains an important health concern in the study area. Occurrence of diarrhea was statistically associated with child age less than or equal to one year, educational status of mother/guardians, and breast feeding. To minimize the magnitude childhood diarrhea, various designing and implementing strategies, such as health education, child care, breast feeding, and weaning practice, integrated with the existing national health extension are quite essential.